2017
DOI: 10.1002/ajh.24771
|View full text |Cite
|
Sign up to set email alerts
|

ABO incompatibility in mismatched unrelated donor allogeneic hematopoietic cell transplantation for acute myeloid leukemia: A report from the acute leukemia working party of the EBMT

Abstract: ABO incompatibility is commonly observed in stem cell transplantation and its impact in this setting has been extensively investigated. HLA-mismatched unrelated donors (MMURD) are often used as an alternative stem cell source but are associated with increased transplant related complications. Whether ABO incompatibility affects outcome in MMURD transplantation for acute myeloid leukemia (AML) patients is unknown. We evaluated 1,013 AML patients who underwent MMURD transplantation between 2005 and 2014. Engraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…Ozkurt et al reported more frequent severe aGVHD among minor ABO-mismatched patients [32], but Kimura et al found a high incidence of severe aGVHD in both major and minor ABO mismatches [33]. There were also conflicting results that failed to find a difference in rates of aGVHD between minor ABO incompatibility and others [3436]. No evidence of an association between the ABO mismatch and cGVHD or survival was observed in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Ozkurt et al reported more frequent severe aGVHD among minor ABO-mismatched patients [32], but Kimura et al found a high incidence of severe aGVHD in both major and minor ABO mismatches [33]. There were also conflicting results that failed to find a difference in rates of aGVHD between minor ABO incompatibility and others [3436]. No evidence of an association between the ABO mismatch and cGVHD or survival was observed in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, an analogous mechanism has been hypothesized to explain the mitigating effect of major ABO-I on severe aGVHD. 6 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Chang et al [23] retrospectively analyzed factors correlating with hematopoietic recovery in 133 pediatric patients (including AML patients) after unmanipulated HLA-mismatched/haplo-identical blood and marrow transplantation; their univariate analysis revealed ABO compatibility was not a risk factor of neutrophil engraftment and platelet engraftment. The study reported by Canaani et al [16] was a retrospective, multicenter study containing 837 AML patients receiving HLA haplo-identical bone marrow or G-CSF mobilized peripheral blood stem cell transplantation. In patients transplanted with bone marrow, minor ABO mismatch was associated with higher incidence of grade II–IV aGVHD and major ABO mismatch was associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%